Revised workflow practices in the management of acute invasive fungal sinusitis during the coronavirus disease 2019 pandemic. Issue 12 (16th December 2022) - Kurien, R; Varghese, L; Cherian, L M; Sundaresan, R; John, M; Mammen, M D; Inja, R R; Manesh, A; Paul, H; Gurijala, P R; Michael, J S; Thomas, M; et al.
Abstract: Objective: To document changes in evaluation protocols for acute invasive fungal sinusitis during the coronavirus disease 2019 pandemic, and to analyse concordance between clinical and histopathological diagnoses based on new practice guidelines. Methods: Protocols for the evaluation of patients with suspected acute invasive fungal sinusitis both prior and during the coronavirus disease 2019 period are described. A retrospective analysis of patients presenting with suspected acute invasive fungal sinusitis from 1 May to 30 June 2021 was conducted, with assessment of the concordance between clinical and final diagnoses. Results: Among 171 patients with high clinical suspicion, 160 (93.6 per cent) had a final histopathological diagnosis of invasive fungal sinusitis, concordant with the clinical diagnosis, with sensitivity of 100 per cent, positive predictive value of 93.6 per cent and negative predictive value of 100 per cent. Conclusion: The study highlights a valuable screening tool with good accuracy, involving emphasis on 'red flag' signs in high-risk populations. This could be valuable in situations demanding the avoidance of aerosol-generating procedures and in resource-limited settings facilitating early referral to higher level care centres.